International licensing and the strengthening of intellectual property rights in developing countries during the 1990s - Park, Walter G.. (OECD Publishing, 2006)
Global intellectual property reform has been underway since the early 1990s (Box 1). With respect to international trade, a central pillar of the reform is the World Trade Organisation's Agreement on Trade-Related Aspects of Intellectual Property Rights Agreement (TRIPS) that came into effect on 1 January 1995. Clearly, a strengthening of intellectual property laws worldwide can benefit those in industrialised nations who own most of the intellectual properties (e.g. copyrights on books, music, and software, patent rights on inventions, and trademark rights on business symbols and names).....
Keywords: Economics